Spontaneous Hemocholecyst in an End-Stage Renal Failure Patient on Low Molecular Weight Heparin Hemodialysis - Konstantinos Blouhos; Konstantinos A. Boulas; Dimitrios G. Tselios; Anestis Hatzigeorgiadis (Case Reports in Surgery)
The present paper describes a case of spontaneous hemocholecyst in a patient with end-stage renal failure on low molecular weight heparin hemodialysis. The patient presented with acute right upper quadrant pain. An initial ultrasound scan demonstrated a distended gallbladder containing echogenic bile without stones. During hospitalization the patient became febrile, and jaundiced, developed leukocytosis, and had an elevation in serum bilirubin, transaminases, and alkaline phosphatase. A new ultrasound demonstrated a thick-walled gallbladder containing echogenic bile and pericholecystic fluid. MRI depicted a distended gallbladder containing material of mixed signal intensity and a normal biliary tract. Open cholecystectomy revealed a gallbladder filled with blood and clots, and transcystic common bile duct exploration flushed blood clots out of the bile duct. To our knowledge this is the second case of spontaneous hemocholecyst reported in the literature as a consequence of uremic bleeding and LMWH hemodialysis in the absence of other pathology.